THE ROLE OF SOCIAL MEDIA IN OVERCOMING THE PROBLEM OF POLITICAL POLARIZATION DURING ELECTIONS - Ade Risna Sari; Pahmi; Maryam Salampessy; Rieneke Ryke Kalalo; Arief Fahmi Lubis (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2024)
During the General Election, the problem of political polarization is a recurring problem and must be resolved immediately. To overcome this problem, the role of social media is very necessary. Based on this, this research aims to analyze the role of social media in overcoming the problem of political polarization during the General Election. This research is qualitative research with a descriptive approach. The data used in this research is secondary data obtained from scientific journals, books, websites and all sources that should be used in every research. The results of this research show that first, social media is like a knife that can become a weapon to protect yourself and others and can also injure yourself and those around you. Second, polarization is caused by ethnic factors, cults, fanaticism and abuse of authority by those in power. Third, social media can play a role by prohibiting campaigns containing SARA, focusing on vision and mission, and increasing educational content.